Use of the amniotic membrane as a dressing material in patient with necrotizing fasciitis: A case report - Álvarez-Ccorimanya , Angela Bepsi (2023)
Introduction: Necrotizing fasciitis is a serious infection that involves the skin, the subcutaneous tissue, and the superficial-deep fascia, it progresses very quickly, and if not treated in time it can cause death. Report case: We present the case of an adult patient with a history of anemia, who was diagnosed with odontogenic necrotizing fasciitis, for which she underwent surgery and underwent intraoral and extraoral drainage plus escharectomy. In addition, pharmacological treatment (intravenous antibiotics) was administered, and an amniotic membrane was placed as a dressing material to reconstruct the hemorrhagic surface left by the necrotizing fasciitis. Conclusions: The amniotic membrane as a dressing material presented favorable results in the patient, obtaining a rapid regeneration of the sequel produced by necrotizing fasciitis.